Mendeteksi Kematangan Pada Buah Mangga Garifta Merah Dengan Transformasi Ruang Warna HSI - Ahmad Muslih Syafi’i; Muhammad Fajar Ahadi; Muhammad Iqbal Rasyid; Faisal Dharma Adhinata; Apri Junaidi (Journal of Applied Informatics and Computing, 2021)
Garifta Mango is obtained from the combination of the best quality local mangoes. Garifta mango is said to have a sweeter taste variant than the quality of other types of mango. However, when choosing Red Garifta mangoes with a good level of ripeness, we are often confused. Sometimes Red Garifta mango entrepreneurs still use manual methods to distinguish the ripeness of Red Garifta mangoes. Therefore, this study carried out a systematic design using the HSI color space transformation method. We used 15 Red Garifta mangoes as test data and 30 Red Garifta mangoes as training data in the testing phase. After doing the test, we get the accuracy, precision, and recall of 15 test data, respectively 80%, 80%, and 87%. From this percentage value, it can be concluded that the method we use can be used to detect the ripeness of the Red Garifta mango fruit.